Functional differentiation of 3-ketosteroid Δ(1)-dehydrogenase isozymes in Rhodococcus ruber strain Chol-4 - Guevara, Govinda (Microb Cell Fact, 2017)
BACKGROUND: The Rhodococcus ruber strain Chol-4 genome contains at least three putative 3-ketosteroid Δ(1)-dehydrogenase ORFs (kstD1, kstD2 and kstD3) that code for flavoenzymes involved in the steroid ring degradation. The aim of this work is the functional characterization of these enzymes prior to the developing of different biotechnological applications. RESULTS: The three R. ruber KstD enzymes have different substrate profiles. KstD1 shows preference for 9OHAD and testosterone, followed by progesterone, deoxy corticosterone AD and, finally, 4-BNC, corticosterone and 19OHAD. KstD2 shows maximum preference for progesterone followed by 5α-Tes, DOC, AD testosterone, 4-BNC and lastly 19OHAD, corticosterone and 9OHAD. KstD3 preference is for saturated steroid substrates (5α-Tes) followed by progesterone and DOC. A preliminary attempt to model the catalytic pocket of the KstD proteins revealed some structural differences probably related to their catalytic differences. The expression of kstD genes has been studied by RT-PCR and RT-qPCR. All the kstD genes are transcribed under all the conditions assayed, although an additional induction in cholesterol and AD could be observed for kstD1 and in cholesterol for kstD3. Co-transcription of some correlative genes could be stated. The transcription initiation signals have been searched, both in silico and in vivo. Putative promoters in the intergenic regions upstream the kstD1, kstD2 and kstD3 genes were identified and probed in an apramycin-promoter-test vector, leading to the functional evidence of those R. ruber kstD promoters. CONCLUSIONS: At least three putative 3-ketosteroid Δ(1)-dehydrogenase ORFs (kstD1, kstD2 and kstD3) have been identified and functionally confirmed in R. ruber strain Chol-4. KstD1 and KstD2 display a wide range of substrate preferences regarding to well-known intermediaries of the cholesterol degradation pathway (9OHAD and AD) and other steroid compounds. KstD3 shows a narrower substrate range with a preference for saturated substrates. KstDs differences in their catalytic properties was somehow related to structural differences revealed by a preliminary structural modelling. Transcription of R. ruber kstD genes is driven from specific promoters. The three genes are constitutively transcribed, although an additional induction is observed in kstD1 and kstD3. These enzymes have a wide versatility and allow a fine tuning-up of the KstD cellular activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-017-0657-1) contains supplementary material, which is available to authorized users.